The Effect of Consuming Dates on Increasing Hemoglobin Levels in Pregnant Women - Sunarni, Neli; Litasari, Resna; Rizqiyani, Annisa Tsania (LPPM STIKes Muhammadiyah Ciamis, 2024)
Introduction: Anemia is one of the causes of antepartum or postpartum bleeding. Anemia in pregnant women occurs if the hemoglobin level in the blood is <11 gr/dl in the first and third trimesters of pregnancy, and if it is <10.5 gr/dl in the second trimester of pregnancy. The impacts that will occur if a pregnant woman is anemic are birth with LBW, prematurity, neonatal death, neonatal anemia, birth by cesarean section, mental development barriers, and low APGAR scores. The incidence of anemia in pregnant women in Indonesia is still relatively high, namely 48.9%. Objective: The aim of this research is to examine further the effect of consuming dates on increasing hemoglobin levels in pregnant women. Method: The method of this research is a review of articles regarding consumption of dates on increasing hemoglobin in pregnant women. Search for articles in English or Indonesian that are accessed by internet searches from databases, including Pubmed and Google Scholar with the keywords dates palm, anemia pregnant. The search process that met the requirements according to the inclusion and exclusion criteria was 5 articles. Result: Consuming dates for pregnant women with anemia can increase hemoglobin levels. The average results of hemoglobin levels showed an increase after consuming dates. Conclusion: Consuming dates for pregnant women can increase hemoglobin levels. Pregnant women should regularly consume dates.